Development of friction stir processing of CNT - reinforced aluminum alloy composites - Regensburg, Anna (2012)
Owing their wide range of exceptional properties, for example thermal conductivity values of more than 3000W/(mK) and strength in the range of 100 GPa, Carbon Nanotubes (CNTs) have recently gained much attention as reinforcement for composite materials. Considering the practical application in metal matrix composites (MMCs), tranferring those favourable properties from nano to macro scale represents a main challenge. Methods of the powder metallurgy route show promising results so far, but also lead to long process times and damage of the tublar structure of the CNTs due to prolonged ball milling times. At this point, the application of Friction Stir Processing (FSP) for fabricating CNT-reinforced MMCs offers the possibility to reduce process times and realize the required reinforcement at the relevant location of the component. The process uses a specially designed tool with a pin to plasticize the base material by frictional heating and thus incorporate the reinforcing material by stirring it into the workpiece. Investigations, that have been carried out on this subject, generally consider the unifom dispersion of the CNTs within the matrix as the key challenge of this process. So far, the solution herefore is the application of multipass-FSP in order to distribute the CNTs uniformly by processing the weld up to five times with alternating welding direction. This method usually leads to damage or even destruction of the tubular structure of the CNTs. Regarding all investigations on this subject, it can be noticed, that only conventional tool profiles like cylindrical or threaded were used for the experiments, though other profiles like square or more complex ones are considered to exhibit an increased mixing effect. Therefore the objective of the thesis is to analyse the performance of four different tool geometries under varying parameters and their influence on the CNT dispersion and general MMC composite properties. Channels were cut into an Al 5086 plate, filled with CNT-powder and processed by the different tools. The results were evaluated by metallographic analysis, hardness and electrical resistance measurement and SEM analysis. Among the different geometries, the triangular profile produced defect-free welds over the whole parameter set and distributed the CNTs uniformly along a wide area close to the weld surface.